Alcohol industry strategies to influence the reform of the Finnish Alcohol Law. Issue 6 (December 2019) - Sama, Thomas Babila; Hiilamo, Heikki
Aim: The aim of this study was to investigate the strategies used by the alcohol industry to influence the reform of the Alcohol Act in Finland during the preparation phase between 2016 and 2017. The study answers the following research question: what strategies were used by the alcohol industry to change the original purpose of the reform on alcohol in Finland? Method: Primary data were collected through 16 expert interviews with experts who had participated in the preparation of the alcohol reform in Finland, while secondary data were collected from prior literature, journal articles and Google databases. Results: The results identified three main political strategies used by the alcohol industry to influence the reform of the law on alcohol in Finland during the preparation phase between 2016 and 2017: "information", under which the alcohol industry lobbied politicians in Parliament through Members of Parliament of the National Coalition Party due to the close ties between the two; "constituency building", under which the alcohol industry formed alliances with interest groups in the grocery-retail business in Finland, to advocate for liberalisation of the law, as well as the use of social media – specifically Twitter – to lobby the public; and lastly, "policy substitution" to promote self-regulation. Conclusions: The results suggest that the involvement of the alcohol industry in political decision-making following Finland's EU membership has given the industry legitimacy and new opportunities to influence alcohol policy, while limiting policies to protect the public from alcohol-related harms. The results may be useful to alcohol policy-makers.